Pengaruh Lingkungan Kerja dan Kesehatan Kerja terhadap Keselamatan Kerja Karyawan pada Gudang PT Datascrip Pulogadung Jakarta Timur - Dimas Agung Riyadi; Tungga Buana Irfana; Tungga Buana Diana (STIKes Ibnu Sina Ajibarang, 2024)
A work environment condition can be said to be good if employees can carry out activities optimally, healthily, safely and comfortably. Effective communication is very important in the company to ensure that superiors and subordinates are open and transparent. Employee appreciation often occurs in every company for employees who have contributed to the company. Career paths in the company are usually seen from the employee's job performance. Therefore, the company must pay attention to a good work environment or create working conditions or a comfortable working atmosphere in order to be able to provide motivation to work, it will have an influence on the enthusiasm and enthusiasm of employees to work. The hope is that the company must build a pleasant work environment so that every employee is happy to do his job so that he can work optimally. A pleasant work environment, cooperative coworkers, and leaders who always pay attention to the complaints of employees are a dream for employees so that employees can work more enthusiastically and have a high commitment to the company.